Desenvolvimento de arcabouço cardíaco derivado de órgão descelularizado - Silva, Flavia Medina da (2016)
Heart disease is considered leading cause of death worldwide and for many patients the only possible treatment is a transplant organ. The tissue engineering came like a way to help in shortage of donor organs, using techniques that consist of removing the organ cells maintaining the components of the extracellular matrix (ECM) and recelularizar with patients own cells, thereby reducing the concentration of immunologically active molecules. All agents used in decellularization alter the composition and cause some damage to the ultrastructure. The objective of this work was the development of a cardiac framework derived extracellular matrix (ECM) decellularized with use of two agents and exposure time reduced. As experimental model were used 14 male Wistar rats aged two months weighing on average 330g. After anesthesia (Ketamine / Xylazine 90 mg / kg / 10 mg / kg), animals had their open chest and removed heart. Their was cannulated and perfused through the ascending aorta initially with PBS, followed by perfusion with 1% SDS detergent and 1% Triton X100. Optical microscopy techniques were used after which the samples processed were stained with hematoxylin and eosin (HÐ), Picrosirius and labeled with fibronectin and laminin antibodies. For transmission electron microscopy and scanning electron microscopy samples were processed after images obtained in their microscopes. Quantification of DNA was done using DNeasy kit and the samples between groups were considered significant at p <0.05 using Student's t test. It was found from the absence of cells in decellularized scaffolds, observed by optical microscopy and maintenance of the ECM scaffold structure was viewed macroscopically and microscopically where it was revealed change in microstructure. The major components of the ECM remained in the decellularized scaffold and DNA concentration decreased by 87.04% comparing control groups and decellularized. With use of only two agents, and reducing the time of exposure process remained effective in the removal of cells, better preservation of ECM components, and may utilize the scaffolds for repopulation.